Penegasan Politik Hukum Desentralisasi Asimetris dalam Rangka Menata Hubungan Pemerintah Pusat dengan Pemerintah Daerah di Indonesia - Kadek Cahya Susila Wibawa (Administrative Law and Governance Journal, 2019)
Abstract The legal politics of Article 18, Article 18A and Article 18B of the UUDNRI 1945 (Indonesian Constitution) do not strictly state that Indonesia adheres to the concept of asymmetric decentralization in the administration of local government. Until now, Indonesia does not yet have a grand design of asymmetric decentralization policy. The asymmetrical idea runs by itself without having its main design. Indonesia needs to affirm its asymmetrical decentralization policy to ensure the implementation of local government by the politic of law in the UUDNRI 1945. The establishment of a basic law on asymmetric decentralization is one way to emphasize that Indonesia adheres to asymmetric devolution in the operation of central government relations with local governments. The construction of the act that is built remains in the spirit of decentralization rather than centralization is carried out asymmetrically rather than symmetrically, and remains within the framework of the United States of the Republic of Indonesia. The act becomes the lex genres of all laws relating to the broadest local autonomy and special autonomy. Keywords: Asymmetric Decentralization, Local Government, Central Government, Autonomy. Abstrak Politik hukum Pasal 18, Pasal 18A, dan Pasal 18B UUDNRI 1945 menyatakan secara tidak tegas bahwa Indonesia menganut konsep desentralisasi asimetris dalam penyelenggaraan pemerintahan daerah. Indonesia sampai saat ini belum memiliki grand design kebijakan desentralisasi asimetris. Konsep asimetris berjalan dengan sendirinya tanpa ada design utamanya. Indonesia perlu penegasan kebijakan desentralisasi asimetris untuk menjamin penyelenggaraan pemerintahan daerah sesuai politik hukum dalam UUDNRI 1945. Pembentukan undang-undang pokok mengenai desentralisasi asimetris merupakan salah satu cara untuk menegaskan bahwa Indonesia menganut desentralisasi asimetris dalam penyelenggaraan hubungan pemerintah pusat dengan pemerintah daerah. Konstruksi undang-undang yang dibangun tetap dengan semangat desentralisasi bukan sentralisasi, dijalankan secara asimetris bukan simetris dan tetap dalam bingkai Negara Kesatuan Republik Indonesia. Undang-undang tersebut menjadi lex generelis dari semua undang-undang yang terkait dengan otonomi daerah seluas-luasnya, otonomi khusus, dan otonomi istimewa. Kata kunci: Desentralisasi Asimetris, Pemerintah Daerah, Pemerintah Pusat, Otonomi.